Scale-Invariant Behavior in a Spatial Game of Prisoners’ Dilemma - LIM, Yun Fong (Institutional Knowledge at Singapore Management University, 2002)
A spatially extended version of the game of prisoner’s dilemma, originally proposed by Nowak and May, is modified to include stochastic updating and found to exhibit scale-invariant behavior. Two critical regimes with different scaling behaviors are found; the corresponding exponents have been determined numerically. Spatially, the critical states are characterized by the existence of delicately balanced networks of defectors separating domains of cooperators; temporally, the evolution of the critical states following local perturbations is characterized by avalanches of various magnitudes, which cause restructuring of the networks of defectors on all scales.